The association of perioperative serum uric acid variation with in-hospital adverse outcomes in coronary artery bypass grafting patients - Gao, Junyi; Cheng, Yi (Frontiers in Cardiovascular Medicine, 2024)
Abstract： Background: Previous studies proposed the predictive value of baseline serum uric acid (SUA) on prognosis of coronary artery bypass grafting (CABG) patients. Association of perioperative SUA variation with in-hospital adverse outcomes of CABG patients is unknown. Methods: 2453 patients were included and divided into four groups (G1-G4) according to perioperative SUA variation (ΔSUA). (G1:ΔSUA ≤ -90μmol/L, G2:-90μmol/L <ΔSUA < 0, G3: 0 ≤ΔSUA < 30μmol/L, G4: 30μmol/L ≤ΔSUA.) Basic characteristics and incidence of adverse outcomes were compared among the groups in the overall population and the subgroups. Multivariate logistic regression was performed to explore the association between perioperative SUA increase and adverse outcomes and receiver operating characteristic (ROC) analysis was used to find the cut-off value of SUA increase. Results: The patients had a mean age of 60.9 years and the majority were males (76.7%). In the group with the most significant increase in SUA (G4), incidences of in-hospital all-cause death and fatal arrhythmia were higher than other groups in the overall population and the subgroups. Multivariate logistic regression showed that SUA level increase ≥ 30µmol/L was significantly associated with in-hospital all-cause death and fatal arrhythmia independent of baseline SUA level and renal function. This association was significant in most subgroups for in-hospital fatal arrhythmia and in ≥ 60 years, myocardial infarction (MI) and female subgroups for in-hospital all-cause death. The cut-off value of SUA increase in the overall population was 54.5µmol/L for in-hospital all-cause death and 42.6µmol/L for in-hospital fatal arrhythmia. Conclusions: Perioperative SUA increase significantly correlated with higher incidence of in-hospital all-cause death and fatal arrhythmia in CABG patients independent of baseline SUA level and renal function. Perioperative SUA variation may provide complementary information in identification of potential patients at risk.